Impact of a Digital Platform for Wildlife Information Management in the Cerro Blanco Protected Forest of Guayaquil Using Plithogenic Statistics - Sonia Jacqueline Tigua Moreira; Edison Luis Cruz Navarrete; Diana Lucia Tigua Moreira; Pedro Manuel García Arias (Neutrosophic Sets and Systems)
Protected areas, such as the 6078-hectare Cerro Blanco Protected Forest of Guayaquil, often struggle with inefficient wildlife information management, including previously physical and inefficient methods of fauna control, which can hinder effective conservation. Comprehensive digital resources are needed to improve data accessibility for informed decision-making regarding conservation activities. This project addressed this opportunity by developing and evaluating a digital platform specifically designed to facilitate the collection, organization, and dissemination of wildlife-based resources. While the consideration of digital approaches in conservation is rapidly increasing, there are minimal articles focused on successful encompassing digital platforms, and none that assess their real-world effect via plithogenic analysis. Therefore, this digital application, which includes functional modules for security, fauna information, a digital catalog, and incident reporting, was implemented in the Cerro Blanco Protected Forest. Its real-world effect was subsequently assessed using plithogenic analysis, a method chosen to provide quantifiable evidence of its success. The results indicate a highly significant positive sentiment from users toward the post-application functionality and the standardization of faunal resources. In addition, the plithogenic analysis produced more statistically significant emergent trends and occurrences due to the information being housed in one collected location. Thus, this study contributes theoretically to the literature by acknowledging the digital application as a practical integration model for wildlife resource management, and practically it applies the application itself as an effective tool for any protected area to achieve higher resource management efficiency.